SUMO conjugation to the pattern recognition receptor FLS2 triggers intracellular signalling in plant innate immunity. Issue 1 (December 2018) - Orosa, Beatriz; Yates, Gary; Verma, Vivek; Srivastava, Anjil; Srivastava, Moumita; Campanaro, Alberto; Vega, Daniel; Fernandes, Alanna; Zhang, Cunjin; Lee, Jack; Bennett, Malcolm; Sadanandom, Ari
Abstract Detection of conserved microbial patterns by host cell surface pattern recognition receptors (PRRs) activates innate immunity. The FLAGELLIN-SENSITIVE 2 (FLS2) receptor perceives bacterial flagellin and recruits another PRR, BAK1 and the cytoplasmic-kinase BIK1 to form an active co-receptor complex that initiates antibacterial immunity inArabidopsis . Molecular mechanisms that transmit flagellin perception from the plasma-membrane FLS2-associated receptor complex to intracellular events are less well understood. Here, we show that flagellin induces the conjugation of the SMALL UBIQUITIN-LIKE MODIFIER (SUMO) protein to FLS2 to trigger release of BIK1. Disruption of FLS2 SUMOylation can abolish immune responses, resulting in susceptibility to bacterial pathogens inArabidopsis . We also identify the molecular machinery that regulates FLS2 SUMOylation and demonstrate a role for the deSUMOylating enzyme, Desi3a in innate immunity. Flagellin induces the degradation of Desi3a and enhances FLS2 SUMOylation to promote BIK1 dissociation and trigger intracellular immune signalling. The plant FLS2 receptor initiates bacterial immunity in response to flagellin. Here the authors show that SUMO conjugates to FLS2 in response to flagellin promoting downstream signalling events while Desi3A, an FLS2 deSUMOylating enzyme, is degraded to enhance immune responses.